Analisis Potensi Sektor Ekonomi Dalam Upaya Peningkatan Pertumbuhan Ekonomi (Studi Empiris Pada Kabupaten dan Kota di Provinsi Gorontalo tahun 2012-2016) - Ismail Ibrahim (Universitas Gorontalo, 2018)
Analysis of Economic Sector Potential in Efforts to Increase Economic Growth (Empirical Study on Gorontalo Regency and Gorontalo City in Gorontalo Province in 2012-2016).The purpose of this study is to analyze the potential of the economic sector in the development of Gorontalo Province, and To identify potential economic sectors with competitive advantage and specialization in Gorontalo Province. This research used the method is LQ (location Quotienf) and Shift Share (SS) analysis to identify economic sector in Gorontalo Province development, identifying potential sectors with competitive advantage. Aided by a time series of data that looks at GDP growth between the study area and the reference area. The result of research shows that in Gorontalo regency, the period of 2012-2016 which becomes the main base sector is agriculture sector, while for Gorontalo city which become the main base sector is gas and water supply sector, building sector and trade sector of hotel and restaurant. In addition, the sector contributes the largest as a contribution to the GDP and absorbing labor in the regency and municipalities so as to encourage the growth of GRDP value every year in the Province of Gorontalo